Extracting Equivalent SQL from Imperative Code in Database Applications - Emani, Venkatesh; Ramachandra, Karthik; Bhattacharya, Subhro; Sudarshan, S. (SIGMOD, 2016)
Optimizing the performance of database applications is an area of practical importance, and has received significant attention in recent years. In this paper we present an approach to this problem which is based on extracting a concise algebraic representation of (parts of) an application, which may include imperative code as well as SQL queries. The algebraic representation can then be translated into SQL to improve application performance, by reducing the volume of data transferred, as well as reducing latency by minimizing the number of network round trips. Our techniques can be used for performing optimizations of database applications that techniques proposed earlier cannot perform. The algebraic representations can also be used for other purposes such as extracting equivalent queries for keyword search on form results. Our experiments indicate that the techniques we present are widely applicable to real world database applications, in terms of successfully extracting algebraic representations of application behavior, as well as in terms of providing performance benefits when used for optimization.